Effect of needle size on immunogenicity and reactogenicity of vaccines in infants: randomised controlled trial. - Diggle, L; Deeks, J; Pollard, A (2006)
OBJECTIVES: To assess the immunogenicity of vaccines for infants and to investigate whether the incidence of reactogenicity is reduced after each immunisation dose using needles of varying lengths and gauges. DESIGN: Randomised controlled trial. SETTING: 18 general practices within two UK primary care trusts. PARTICIPANTS: 696 healthy infants vaccinated at 2, 3, and 4 months of age, with follow-up to 5 months of age. INTERVENTIONS: Combined diphtheria, tetanus, whole cell pertussis, and Haemophilus influenzae type b vaccine and a serogroup C meningococcal glycoconjugate vaccine administered using either a wide, long needle (23 gauge/0.6 mm diameter, 25 mm), a narrow, short needle (25 gauge/0.5 mm diameter, 16 mm), or a narrow, long needle (25 gauge, 25 mm). MAIN OUTCOME MEASURES: Local and general reactions recorded by parents for three days after each dose; and diphtheria, tetanus, and H influenzae type b antibody concentrations and functional antibody against serogroup C Neisseria meningitidis 28-42 days after the third dose. RESULTS: Local reactions to diphtheria, tetanus, whole cell pertussis, H influenzae type b vaccinations decreased significantly with wide, long needles compared with narrow, short needles. At all three doses one less infant experienced local reactions at days 1, 2, or 3 for every six to eight vaccinated. Significantly fewer infants vaccinated with the long needle experienced severe local reactions. Non-inferiority of the immune response was shown using a wide, long needle rather than a narrow, short needle for serogroup C meningococcal glycoconjugate vaccine and for diphtheria but not for H influenzae type b or tetanus, although no evidence was found of a decrease. Little difference was found between needles of the same length but different gauges in local reaction or immune response. CONCLUSIONS: Long (25 mm) needles for infant immunisations can significantly reduce vaccine reactogenicity at each dose while achieving comparable immunogenicity to that of short (16 mm) needles. Trial registration Current Controlled Trials ISRCTN62032215 [controlled-trials.com].